Sądy społeczne w systemie wymiaru sprawiedliwości Niemieckiej Republiki Demokratycznej - Malicka, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Social courts in the German Democratic Republic, as constitutional judicial organs, guaranteed the direct participation of citizens in the exercise of state power. They played an important role in the judicial system and in fact became the courts of the lowest instance. They settled disputes in the field of labour and civil law and adjudicated in cases of violations of criminal law. In retrospect, they can be assessed as a special type of court typical of the socialist system, the decisions of which were primarily of educational and preventive importance.
Keywords: sądy społeczne; socjalistyczny wymiar sprawiedliwości; sędziowie niezawodowi; rozstrzyganie sporów